A polyurethane film for light diffusion and preparation method thereof
The polyurethane film for light diffusion prepared by using polycaprolactone polyol, diisocyanate and other materials of specific ratios has solved the shortcomings in performance and environmental protection of the existing light diffusion films, and achieved high intensity and excellent light diffusion performance, which is suitable for applications in electronic fields and other fields.
Patent Information
- Application Number
- CN202510084103.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing light diffusion films have shortcomings in meeting high performance and environmental protection requirements, and it is difficult to gain advantages in quality and cost. In the context of continuous advancement of liquid crystal display technology, technological innovation and upgrading are needed.
A polyurethane film for light diffusion composed of polycaprolactone polyol, diisocyanate, epoxy resin, natural cellulose, nano-scale transparent ceramic particles, silane coupling agent and antistatic agent are used to improve its tensile strength, viscosity ability and light diffusion properties through specific preparation methods and ratios.
The preparation of high-strength polyurethane film composite materials has been achieved, with better light diffusivity and increased haze by 45.8%, while meeting environmental protection requirements, and has important application prospects, especially in the electronics field.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to a polymer compound, in particular to a polyurethane film for light diffusion and a preparation method thereof. Background Art
[0002] Polyurethane is a polymer material with excellent mechanical properties formed by the polycondensation reaction of polyols and polyisocyanates. It was first developed by German scientists in the 1930s. This material is now widely used, involving products such as coatings, adhesives, fabric finishing agents, leather modifiers, polyurethane soft foam / rigid foam, elastomers, etc. It is widely used in textiles, construction, aviation, shipping, transportation, medicine, electronics and other fields. The main raw materials for its synthesis include diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), and polypropylene glycol (PPG), which have now become international commodities. However, due to the complex synthesis of the raw materials of this product and the different needs of different scenarios, the market is huge, but the competition is also quite fierce.
[0003] Light diffusion film is a film with light diffusion function. It is usually made of polymer materials, which can diffuse light evenly, make the light softer, help improve the display effect, and provide a more comfortable viewing experience. At the same time, it can cover up some surface defects and improve the clarity and contrast of the image. Nowadays, light diffusion film is widely used in different fields: such as posters, brochures, LCDs, LED displays, etc. The current technology is commonly used to use acrylic resin to precisely coat a layer of randomly dispersed micron-structured diffusion particles on the surface of PET with very good transparency. Because the difference in the refractive index of the diffusion particles and polyurethane is large, the light is refracted and diffracted multiple times through the diffusion layer, so that the light of the light source is evenly diffused, making the display softer. However, with the continuous advancement of liquid crystal display technology, the requirements for light diffusion films are getting higher and higher. Continuous innovation and upgrading of light diffusion film technology is required. At the same time, environmental protection requirements must be met, so to a certain extent, the performance improvement and large-scale application of light diffusion films are limited. The market competition is fierce, and if you can gain a greater advantage in quality and cost, it will be beneficial to occupy the market.
[0004] Patent CN111944405B provides a new light diffuser with good leveling properties, making it scratch-resistant, so that the light diffuser in the diffusion film is not easy to fall off. But we know that light diffusion is because when light passes through an inhomogeneous film, scattering occurs due to the different refractive indices of the inhomogeneous phase and the matrix, so when the surface of the matrix is embossed, the light diffusion effect will be enhanced. Therefore, based on this principle, we innovate a more solid, environmentally friendly and highly antistatic light diffusion layer. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a polyurethane film for light diffusion; another purpose of the present invention is to provide a method for preparing a polyurethane film for light diffusion.
[0006] Technical solution: A polyurethane film for light diffusion, comprising the following components in percentage: 20%-40% polycaprolactone polyol, 15%-40% diisocyanate, 5%-10% diethylene glycol, 5%-10% epoxy resin, 0.5%-1% antistatic agent, 1%-2% natural cellulose, 0.5%-1% nano-scale transparent ceramic particles, 1%-3% silane coupling agent, and 0.5% glycerol, wherein the polycaprolactone polyol is a polycaprolactone triol with an average molecular weight of 300.
[0007] Preferably, the natural cellulose is transparentized plant fiber such as cotton or flax.
[0008] Preferably, the nanoscale transparent ceramic is one of Al2O3, CaO, and AlN.
[0009] Preferably, the silane coupling agent is one of γ-aminopropyltriethoxysilane (KH550), γ-glycidyl ether propyltrimethoxysilane (KH560), and γ-(methacryloyloxy)propyltrimethoxysilane (KH570).
[0010] Preferably, the antistatic agent is polyaniline.
[0011] A method for preparing a polyurethane film for light diffusion comprises the following steps:
[0012] S1. Weigh polycaprolactone polyol and diisocyanate according to the formula, dissolve them in anhydrous ethanol, stir and react for 2 hours at a temperature of 40-80° C., then add the formula amount of diethylene glycol and 50% of the formula amount of epoxy resin, continue stirring and reacting for 1-3 hours to obtain a modified polyurethane solution;
[0013] S2, 50% of the formula amount of epoxy resin, the formula amount of natural cellulose, and the silane coupling agent are mixed and added to ethanol, the temperature is set to 50°C, and after stirring evenly, deionized water is added, and the pH of the system is adjusted to 8 with sodium hydroxide solution, and stirred for 30 minutes, and the formula amount of antistatic agent, nano-scale transparent ceramic particles, and glycerol are added, and the mixture is fully stirred evenly, and the pH of the system is adjusted to 5-6 with dilute hydrochloric acid, and filtered. The filter residue is washed once with deionized water, and the filtrate is combined, and the filtrate is decompressed and evaporated to remove the solvent to obtain a light diffusion material;
[0014] S3, spin-coating the polyurethane solution prepared in step S1 on a glass substrate, and curing it by ultraviolet light to obtain a polyurethane film 1;
[0015] S4, dissolving the light diffusing material prepared in step S2 in anhydrous ethanol in an appropriate proportion, evenly applying the material on the polyurethane film 1 prepared in step S3, and curing the film by irradiating the film with ultraviolet light to obtain a light diffusing polyurethane film 2;
[0016] S5, coating another glass plate with silicone oil, and completely covering the side coated with silicone oil on the light diffusing polyurethane film 2 prepared in step S4, compacting, putting into an oven, setting the temperature to 80°C, taking out after drying for 8 hours, removing the glass plate, cleaning the film, and then putting it into a tempering furnace for heat treatment, setting the temperature to 100-120°C, taking it out after the heat treatment is completed and cooling it to 15-25°C;
[0017] S6. Cut into pieces to obtain a polyurethane film for light diffusion.
[0018] Beneficial effects: In the process of synthesizing polyurethane with polycaprolactone polyol and diisocyanate, diethylene glycol can significantly improve the tensile strength and breaking strength of polyurethane products. The tensile strength of ordinary polyurethane is generally about 50MPa, and the tensile strength of the polyurethane of the present invention can reach 213MPa. The ratio of diethylene glycol, polycaprolactone polyol and diisocyanate has a certain influence on the improvement of tensile strength and breaking strength. Epoxy resin can significantly improve the adhesion between different plastics. The present invention adopts transparent ceramics and transparent natural cellulose to increase its light diffusion. Since the surface of transparent ceramics is smooth and the compatibility with polyurethane and epoxy resin is poor, a silane coupling agent is used to treat the surface to improve the strength of the composite material. Other additives are added at the same time, namely, an antistatic agent increases its antistatic property, and glycerol increases the flowability of the material. Using the ratio of this invention, a high-strength polyurethane film composite material can be obtained, and at the same time, the light diffusion is better and the haze is increased by 45.8%. The preparation process of the present invention is simple, and it has very important application prospects, especially in the field of electronic applications. DETAILED DESCRIPTION
[0019] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0020] Embodiment 1:
[0021] Weigh 2.0 kg of polycaprolactone triol (Hunan Juren New Materials Co., Ltd., PCL-3037, average molecular weight 300 g / mol) and 3.0 kg of diisocyanate and dissolve them in anhydrous ethanol. Stir and react for 2 hours at 80 °C, then add 1.0 kg of diethylene glycol and 0.5 kg of epoxy resin, and continue to react for 2 hours under stirring to obtain a modified polyurethane solution. Mix 0.5 kg of epoxy resin, 0.1 kg of transparent cotton fiber, and 0.1 kg of silane coupling agent KH550 and add them to ethanol. Set the temperature to 50 °C, stir evenly, add deionized water, adjust the system pH to 8 with sodium hydroxide solution, and stir for 30 minutes. When the yellowish color on the surface of natural cellulose completely fades, add 0.1kg antistatic agent polyaniline, 0.05kg nano-scale transparent Al2O3 particles, and 0.05kg glycerol, stir well, adjust the pH of the system to 5-6 with dilute hydrochloric acid, filter, wash the filter residue with deionized water once, combine the filtrate and evaporate the solvent under reduced pressure to obtain the light diffusion material for use. Spin-coat the polyurethane solution obtained above three times on the glass substrate, and cure it with ultraviolet light to obtain a polyurethane film. Then dissolve the prepared light diffusion material in anhydrous ethanol, evenly apply it twice on the cured polyurethane film, and irradiate it with ultraviolet light to cure it. After it is completely cured, apply silicone oil to another glass plate, and cover the side coated with silicone oil completely on the prepared film and compact it. Put it in an oven, set the temperature to 80℃, take it out after drying for 8 hours, remove the glass plate, clean the film, and then put it in a tempering furnace for heat treatment, set the temperature to 100℃, and take it out after one hour. Cool to 20℃, then cut it into pieces to test its performance.
[0022] Embodiment 2:
[0023] Weigh 4.0 kg of polycaprolactone triol (Hunan Juren New Materials Co., Ltd., PCL-3037, average molecular weight 300 g / mol) and 4.0 kg of diisocyanate and dissolve them in anhydrous ethanol. Stir and react for 2 hours at 40 °C, then add 0.5 kg of diethylene glycol and 0.25 kg of epoxy resin, and continue to react for 2 hours under stirring to obtain a modified polyurethane solution. Mix 0.25 kg of epoxy resin, 0.2 kg of transparent flax fiber, and 0.3 kg of silane coupling agent KH560 and add them to ethanol. Set the temperature to 50 °C, stir evenly, add deionized water, adjust the system pH to 8 with sodium hydroxide solution, and stir for 30 minutes. When the yellowish color on the surface of natural cellulose completely fades, add 0.1kg antistatic agent polyaniline, 0.05kg nano-scale transparent CaO particles, and 0.05kg glycerol, stir well, adjust the pH of the system to 5-6 with dilute hydrochloric acid, filter, wash the residue with deionized water once, combine the filtrate and evaporate the solvent under reduced pressure to obtain the light diffusion material for use. Spin coat the polyurethane solution obtained above on the glass substrate four times, and cure it with ultraviolet light to obtain a polyurethane film. Then dissolve the prepared light diffusion material in anhydrous ethanol, evenly apply it twice on the cured polyurethane film, and irradiate it with ultraviolet light to cure it. After it is completely cured, apply silicone oil to another glass plate, and cover the side coated with silicone oil completely on the prepared film and compact it. Put it in an oven, set the temperature to 80℃, take it out after drying for 8 hours, remove the glass plate, clean the film, and then put it in a tempering furnace for heat treatment, set the temperature to 120℃, and take it out after one hour. Cool to 25℃, then cut it into pieces to test its performance.
[0024] Embodiment 3:
[0025] Weigh 2.0 kg of polycaprolactone triol (Hunan Juren New Materials Co., Ltd., PCL-3037, average molecular weight 300 g / mol) and 3.0 kg of diisocyanate and dissolve them in anhydrous ethanol. Stir and react at 80 °C for 2 hours, then add 1.0 kg of diethylene glycol and 0.5 kg of epoxy resin, and continue to react for 2 hours under stirring to obtain a modified polyurethane solution. Mix 0.5 kg of epoxy resin, 0.1 kg of transparent cotton fiber, and 0.1 kg of silane coupling agent KH570 and add them to ethanol. Set the temperature to 50 °C, stir evenly, add deionized water, adjust the system pH to 8 with sodium hydroxide solution, and stir for 30 minutes. When the yellowish color on the surface of natural cellulose completely fades, add 0.1kg antistatic agent polyaniline, 0.05kg nano-scale transparent AlN particles, and 0.05kg glycerol, stir well, adjust the pH of the system to 5-6 with dilute hydrochloric acid, filter, wash the filter residue with deionized water once, combine the filtrate and evaporate the solvent under reduced pressure to obtain the light diffusion material for use. Spin-coat the polyurethane solution obtained above on the glass substrate five times, and cure it with ultraviolet light to obtain a polyurethane film. Then dissolve the prepared light diffusion material in anhydrous ethanol, evenly apply it twice on the cured polyurethane film, and irradiate it with ultraviolet light to cure it. After it is completely cured, apply silicone oil to another glass plate, and cover the side coated with silicone oil completely on the prepared film and compact it. Put it in an oven, set the temperature to 80℃, take it out after drying for 8 hours, remove the glass plate, clean the film, and then put it in a tempering furnace for heat treatment, set the temperature to 100℃, and take it out after one hour. Cool to 20℃, then cut it into pieces to test its performance.
[0026] Embodiment 4:
[0027] Weigh 2.0 kg of polycaprolactone triol (Hunan Juren New Materials Co., Ltd., PCL-3037, average molecular weight 300 g / mol) and 3.0 kg of diisocyanate and dissolve them in anhydrous ethanol. Stir and react at 80 °C for 2 hours, then add 1.0 kg of diethylene glycol and 0.5 kg of epoxy resin, and continue to react for 2 hours under stirring to obtain a modified polyurethane solution. Mix 0.5 kg of epoxy resin, 0.1 kg of transparent flax fiber, and 0.1 kg of silane coupling agent KH560 and add them to ethanol. Set the temperature to 50 °C, stir evenly, add deionized water, adjust the system pH to 8 with sodium hydroxide solution, and stir for 30 minutes. When the yellowish color on the surface of natural cellulose completely fades, add 0.1kg antistatic agent, 0.05kg nano-scale transparent Al2O3 particles, and 0.05kg glycerol, stir well, adjust the pH of the system to 5-6 with dilute hydrochloric acid, filter, wash the filter residue with deionized water once, combine the filtrate and evaporate the solvent under reduced pressure to obtain the light diffusion material for use. Spin-coat the polyurethane solution obtained above on the glass substrate six times, and cure it with ultraviolet light to obtain a polyurethane film. Then dissolve the prepared light diffusion material in anhydrous ethanol, evenly apply it twice on the cured polyurethane film, and irradiate it with ultraviolet light to cure it. After it is completely cured, apply silicone oil to another glass plate, and cover the side coated with silicone oil completely on the prepared film and compact it. Put it in an oven, set the temperature to 80℃, take it out after drying for 8 hours, remove the glass plate, clean the film, and then put it in a tempering furnace for heat treatment, set the temperature to 100℃, and take it out after one hour. Cool to 20℃, then cut it into pieces to test its performance.
[0028] Comparative Example:
[0029] 3.0kg of polycaprolactone triol (Hunan Juren New Materials Co., Ltd., PCL-3037, average molecular weight 300g / mol) and 4.5kg of diisocyanate were dissolved in anhydrous ethanol, stirred and reacted at 80℃ for 2 hours, and then 1.0kg of diethylene glycol and 0.5kg of epoxy resin, 0.1kg of nano-silicon dioxide, 0.5kg of epoxy resin, and 0.2kg of silane coupling agent KH550 were added, mixed and stirred together, reacted for two hours, coated on the glass plate three times, put into the oven, set the temperature to 80℃, took out after 8 hours, removed the glass plate, cleaned it, and then put it into the tempering furnace for heat treatment, set the temperature to 100℃, and took it out after two hours. Cool to 20℃ and then cut into pieces, and test its performance.
[0030] The performance test results of the light diffusion polyurethane films obtained in Examples 1 to 4 and the comparative example are shown in the following table:
[0031]
[0032] From the above table, we can see that when the thickness of the film is gradually increased from Example 1 to Example 4, its light transmittance gradually decreases, but the overall increase in haze is not obvious. In the comparative example, we can easily find that compared with the light diffusion film preparation method of the existing formula, the light diffusion film of the present invention has great advantages in terms of material strength and diffusion performance compared with the comparative example. In terms of environmental protection of raw materials, we also comply with the existing green development concept. Various experimental data show that the performance of the present invention is excellent and has high practicality.
[0033] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polyurethane film for light diffusion, characterized in that: The formula includes the following components by weight percentage: 20%-40% polycaprolactone polyol, 15%-40% diisocyanate, 5%-10% diethylene glycol, 5%-10% epoxy resin, 0.5%-1% antistatic agent, 1%-2% natural cellulose, 0.5%-1% nano-scale transparent ceramic particles, 1%-3% silane coupling agent, and 0.5% glycerol, wherein the polycaprolactone polyol is polycaprolactone triol with an average molecular weight of 300 g / mol; The preparation method of the light diffusion polyurethane film is as follows: S1. Weigh polycaprolactone polyol and diisocyanate according to the formula, dissolve them in anhydrous ethanol, stir and react for 2 hours at a temperature of 40-80° C., then add the formula amount of diethylene glycol and 50% of the formula amount of epoxy resin, continue stirring and reacting for 1-3 hours to obtain a modified polyurethane solution; S2, 50% of the formula amount of epoxy resin, the formula amount of natural cellulose, and the silane coupling agent are mixed and added to ethanol, the temperature is set to 50°C, and after stirring evenly, deionized water is added, and the pH of the system is adjusted to 8 with sodium hydroxide solution, and stirred for 30 minutes, and the formula amount of antistatic agent, nano-scale transparent ceramic particles, and glycerol are added, and the mixture is fully stirred evenly, and the pH of the system is adjusted to 5-6 with dilute hydrochloric acid, and filtered. The filter residue is washed once with deionized water, and the filtrate is combined, and the filtrate is decompressed and evaporated to remove the solvent to obtain a light diffusion material; S3, spin-coating the polyurethane solution prepared in step S1 on a glass substrate, and curing it by ultraviolet light to obtain a polyurethane film 1; S4, dissolving the light diffusing material prepared in step S2 in anhydrous ethanol in an appropriate proportion, evenly applying the material on the polyurethane film 1 prepared in step S3, and curing the film by irradiating the film with ultraviolet light to obtain a light diffusing polyurethane film 2; S5, coating another glass plate with silicone oil, and completely covering the side coated with silicone oil on the light diffusing polyurethane film 2 prepared in step S4, compacting, putting into an oven, setting the temperature to 80°C, taking out after drying for 8 hours, removing the glass plate, cleaning the film, and then putting it into a tempering furnace for heat treatment, setting the temperature to 100-120°C, taking it out after the heat treatment is completed and cooling it to 15-25°C; S6. Cut into pieces to obtain a polyurethane film for light diffusion.
2. The light-diffusing polyurethane film according to claim 1, wherein: Natural cellulose is transparent cotton and flax plant fibers.
3. The light-diffusing polyurethane film according to claim 1, wherein The nano-scale transparent ceramic is one of Al2O3, CaO and AlN.
4. The light-diffusing polyurethane film according to claim 1, wherein: The silane coupling agent is one of γ-aminopropyltriethoxysilane (KH550), γ-glycidyl ether propyltrimethoxysilane (KH560), and γ-(methacryloyloxy)propyltrimethoxysilane (KH570).
5. The light-diffusing polyurethane film according to claim 1, wherein: The antistatic agent is polyaniline.
Citation Information
Patent Citations
Preparation method of anti-aging light diffusion film
CN113900169A
High-transparency high-elasticity polyurethane film and preparation process thereof
CN118388741A